Enhanced closed-state inactivation of mutant cardiac sodium channels (SCN5A N1541D and R1632C) through different mechanisms. (May 2019) - Dharmawan, Tommy; Nakajima, Tadashi; Iizuka, Takashi; Tamura, Shuntaro; Matsui, Hiroki; Kaneko, Yoshiaki; Kurabayashi, Masahiko
Abstract: Background: SCN5A variants can be associated with overlapping phenotypes such as Brugada syndrome (BrS), sinus node dysfunction and supraventricular tachyarrhythmias. Our genetic screening of SCN5A in 65 consecutive BrS probands revealed two patients with overlapping phenotypes: one carried an SCN5A R1632C (in domain IV-segment 4), which we have previously reported, the other carried a novel SCN5A N1541D (in domain IV-segment 1). Objective: We sought to reveal whether or not these variants are associated with the same biophysical defects. Methods: Wild-type (WT) or mutant SCN5A was expressed in tsA201-cells, and whole-cell sodium currents (hNav 1.5/INa ) were recorded using patch-clamp techniques. Results: The N1541D-INa density, when assessed from a holding potential of -150 mV, was not different from WT-INa as with R1632C-INa, indicating that SCN5A N1541D did not cause trafficking defects. The steady-state inactivation curve of N1541D-INa was markedly shifted to hyperpolarizing potentials in comparison to WT-INa (V1/2 -WT: –82.3 ± 0.9 mV, n  = 15; N1541D: –108.8 ± 1.6 mV, n  = 26, P  < .01) as with R1632C-INa . Closed-state inactivation (CSI) was evaluated using prepulses of −90 mV for 1460 ms. Residual N1541D-INa and R1632C-INa were markedly reduced in comparison to WT-INa (WT: 63.8 ± 4.6%, n  = 18; N1541D: 15.1 ± 2.3%, n  = 19, P  < .01 vs WT; R1632C: 5.3 ± 0.5%, n  = 15, P  < .01 vs WT). Entry into CSI of N1541D-INa was markedly accelerated, and that of R1632C-INa was weakly accelerated in comparison to WT-INa (tau-WT: 65.8 ± 7.4 ms, n  = 18; N1541D: 13.7 ± 1.1 ms, n  = 19, P  < .01 vs WT; R1632C: 39.5 ± 2.9 ms, n  = 15, P  < .01 vs WT and N1541D). Although N1541D-INa recovered from closed-state fast inactivation at the same rate as WT-INa, R1632C-INa recovered very slowly (tau-WT: 1.90 ± 0.16 ms, n  = 10; N1541D: 1.72 ± 0.12 ms, n = 10, P  = .41 vs WT; R1632C: 53.0 ± 2.5 ms, n  = 14, P  < .01 vs WT and N1541D). Conclusions: Both N1541D-INa and R1632C-INa exhibited marked enhancement of CSI, but through different mechanisms. The data provided a novel understanding of the mechanisms of CSI of INa . Clinically, the enhanced CSI of N1541D-INa leads to a severe loss-of-function of INa at voltages near the physiological resting membrane potential (~–90 mV) of cardiac myocytes; this can be attributable to the patient's phenotypic manifestations. Highlights: Besides SCN5A R1632C, N1541D was identified in a patient with overlapping phenotypes. Closed-state inactivation (CSI) of INa for these two mutants were markedly enhanced. However, the mechanisms of enhanced CSI were different. Entry into CSI of INa for N1541D (in DIV-S1) was markedly accelerated. In contrast, recovery from CSI of INa for R1632C (in DIV-S4) was markedly decelerated.